Pendampingan Optimalisasi Instagram sebagai Media Digital Branding dan Pemasaran pada UMKM Katsu Express - Oktavia Firnanda; Nadzar Al Zamani; Lissa Mukhlishotun Nawa; Devia Nafasya; Muhammad Akbar Bintang (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The development of social media, particularly Instagram, has created significant opportunities for micro, small, and medium enterprises (MSMEs) to strengthen brand image and improve the effectiveness of digital marketing. However, Instagram is often utilized by MSME actors in a limited manner, without clear content planning and communication strategies. This community service activity aims to optimize the use of Instagram as a digital branding and marketing medium for Katsu Express MSME. The method employed is a participatory descriptive approach, implemented through stages of observation, training, mentoring, and evaluation based on Instagram Insights data. The results indicate a significant improvement in the performance of the Katsu Express Instagram account in terms of impressions, audience reach, and user engagement, particularly after the implementation of Instagram Ads. In addition, the partner demonstrated increased understanding and skills in content planning, visual consistency, and the use of Instagram analytics features. This activity proves that structured Instagram optimization through mentoring can enhance brand visibility and support the strengthening of sustainable digital marketing strategies for MSMEs.